Parliamentary Verbatim in Nepal: The Role of Records in Judicial Interpretation (Samsad Journal संसद जर्नल, 2025)
Imagine a courtroom scenario in which the judge explores the discussions, disputes, and compromises that gave rise to the legislation straight out of the halls of the Parliament, rather than only relying on the language of the law. This is the power of parliamentary records, such as the well-known Parliamentary verbatim, which provide a window into the legislative soul by exposing the legislation's underlying meaning and essence and the legislators' intents. Currently, Nepal does not have an extensive record of its legislative history. This essay examines the significant ramifications of this omission. It makes the case that a strong system of legislative record-keeping is essential to good governance and goes beyond administrative effectiveness. This paper makes a strong argument for embracing the authority of parliamentary records by exploring the lengthy history of legislative interpretation, comparing it to common law nations, and examining the particular difficulties Nepal faces.